2006
DOI: 10.1007/s10038-006-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone receptor gene polymorphism and ovarian responses to controlled ovarian hyperstimulation for IVF-ET

Abstract: This study was performed to investigate the association between FSH receptor (FSHR) gene polymorphism at position 680 and the outcomes of controlled ovarian hyperstimulation (COH) for in vitro fertilization and embryo transfer (IVF-ET) in Korean women. Two hundred and sixty-three patients under 40 years of age who underwent IVF-ET procedures were included in this study. Patients with polycystic ovary syndrome, endometriosis, or a previous history of ovarian surgery were excluded. Following extraction of genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
95
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 19 publications
12
95
2
3
Order By: Relevance
“…G −29 A, A 919 G (Thr 307 Ala) and A 2039 G (Asn 680 Ser) polymorphisms have been extensively studied by different investigators. It was reported that the polymorphism A 2039 G is associated with high basal FSH levels in women undergoing Assisted Reproductive Technology (ART) programme [17][18][19][20][21][22]. Recently, we have reported association of FSHR gene polymorphism (A 919 G, G −29 A) with altered ovarian response in subjects undergoing gonadotropin treatment during ART programme [23,24].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…G −29 A, A 919 G (Thr 307 Ala) and A 2039 G (Asn 680 Ser) polymorphisms have been extensively studied by different investigators. It was reported that the polymorphism A 2039 G is associated with high basal FSH levels in women undergoing Assisted Reproductive Technology (ART) programme [17][18][19][20][21][22]. Recently, we have reported association of FSHR gene polymorphism (A 919 G, G −29 A) with altered ovarian response in subjects undergoing gonadotropin treatment during ART programme [23,24].…”
Section: Introductionmentioning
confidence: 94%
“…However, a few studies have refuted this view [22,33]. We have recently reported that alteration at 919 position (Thr 307 Ala) of FSHR gene, is associated with hyper ovarian response [23].…”
Section: Hormonementioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between allelic variants at these positions, the presence of polycystic ovary syndrome (PCOS), and the responsiveness to exogenous FSH have been studied in some ethnic groups [3]. A different responsiveness to FSH according to the allelic variant at position 680 has been repeatedly reported, Ser680 homozygote women being more FSHresistant than women with homozygote Asn680, and heterozygote (Ser680Asn) patients showing an intermediate responsiveness [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%